Search for anomalous kinematics in tt dilepton events at CDF II. - Acosta, D; Adelman, J; Affolder, T; Akimoto, T; Albrow, MG; Ambrose, D; Amerio, S; Amidei, D; Anastassov, A; Anikeev, K; Annovi, A; Antos, J; et al. (2005)
We report on a search for anomalous kinematics of tt dilepton events in pp collisions at square root of s=1.96 TeV using 193 pb(-1) of data collected with the CDF II detector. We developed a new a priori technique designed to isolate the subset in a data sample revealing the largest deviation from standard model (SM) expectations and to quantify the significance of this departure. In the four-variable space considered, no particular subset shows a significant discrepancy, and we find that the probability of obtaining a data sample less consistent with the SM than what is observed is 1.0%-4.5%.